The Interactive Whiteboard: Components, Settings, Posibilities, and Singularities - Aguilar Álvarez, Rolando (2014)
In recent years, Interactive Whiteboards (IWB) have gained a respected space within the academic practitioners in the university context. In this article, we will do a revision of these devices going from their main components, their implications in the teaching-learning process within Higher Education Institutions (HEI) and the way they can be configured in the classroom. We also reflect on the academic possibilities generated from their use and how their components may enhance the classroom experience. In this way –and reflecting upon given specific situations– we compare the singularities of different configurations of the IWB components and the implications for their integration in HEI as justified and useful didactic resources.